Effect of slow breathing exercise on non linear Heart rate variability in transfusion dependent thalassemic patients - Das, Kamol Chandra; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2019)
Background: Nonlinear measure of heart rate variability (HRV) is an emerging tool to detect changes in cardiac autonomic nerve function (CANF) in transfusion dependent thalassemic (TDT) patients. Slow breathing exercise (SBE) can significantly improve HRV in health and various diseases. Objective: To observe the effect of slow breathing exercise (SBE) on non linear measures of HRV in TDT patients. Methods: This prospective interventional study was done in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka in 2018 on 60 male TDT patients aged 15-30 years. Thirty patients received conventional treatment and 30 patients performed slow breathing exercise along with the conventional treatment for 3 months. Age and sex matched 30 healthy control were enrolled. All subjects were followed up at baseline and after 3 months. Non linear (Poincare) HRV parameters were recorded by Power Lab 8/35 AD Instrument, Australia. For statistical analysis paired sample ‘ t’ test and independent sample ‘t’ test were used. Result: SD1, SD2 and SD1/SD2 were found significantly lower in TDT patients compared to healthy control at baseline. After 3 months of slow breathing exercise, significant increment of these parameters occurred with trend of improvement in cardiac autonomic nerve function in this group of patients. Conclusion: Slow breathing exercise may improve cardiac autonomic nerve function and sympathovagal balance in transfusion dependent thalassemic patients. J Bangladesh Soc Physiol. 2019, June; 14(1): 26-32